Poverty in Africa: Causes, Consequences, and Potential Solutions - Akello Barke (International Journal of Science and Society, 2023)
Africa, the world's second-largest continent both in terms of landmass and population, stands as a paradox of untapped potential and enduring challenges. Amidst its breathtaking landscapes and cultural richness, it grapples with a persistent and pervasive issue: poverty. This journal article delves into the multifaceted problem of poverty in Africa, offering a comprehensive exploration of its underlying causes, profound consequences, and a range of potential solutions. Poverty in Africa is not just an economic quandary; it is a complex, interwoven issue with social, political, and historical dimensions that necessitate a nuanced understanding and collaborative efforts from both African nations and the international community.